Pengembangan Sistem Monitoring pada Identifikasi Kesehatan Pencernaan menggunakan Bluetooth Low Energy (BLE) berbasis Aplikasi Smartphone - Ryan Anggito Priono; Barlian Henryranu Prasetio; Eko Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
A research with the title â€œIdentification System for Digestive Health by Bowel Sound using Convolutional Neural Networkâ€ is a research done by a college student named Ryzaldi Ananda Fabiana with the purpose of making a system that could detect ileus obstruction from the person's gastrointestinal sound. But, the implementation of the system uses VNC viewer as an application which needs internet connection to run and showing the result of identification on the raspberry pi's terminal. A solution to the problem is to create a specific application from scratch specifically for the system using a protocol that doesn't require any internet such as BLE or Bluetooth Low Energy. This research will modify the previous research's raspbberry pi untuk a BLE peripheral and create and application that will run as a BLE central that will initiate the connection with the raspberry pi. The system works by initiating a connection between the application and raspberry pi where from the application side it will show every service and characteristic that is initialized on the raspberry pi side and includes several buttons to call the identification functions, merge and downsample the signal data and send the data. This study found that the average time it took for the application and raspberry pi to finish creating a connection or the delay is about 2.060369 seconds, sending a message has an average delay of 0.190982 seconds and sending data has an average delay of 0.0564674 seconds.